Exploring the Antibacterial Activity of Ipomoea staphylina Extracts Against H. pylori: A Pharmacognostic Investigation of Whole Plant and Matured Stem with Emphasis on Quercetin Isolation - Lakshmanan Narayanan; Suseem S R (Tropical Life Sciences Research, 2024)
Ipomoea staphylina Rome & Schult, entrenched in ethnomedicinal practices, is recognised for its efficacy in treating stomach disorders. Traditionally used in Dharmapuri, Tamil Nadu for stomach ulcers, its matured stem bark latex is therapeutically relevant, especially for Helicobacter pylori (H. pylori) infections. This prompts scientific exploration into its antibacterial properties. The research validates the antibacterial efficacy of I. staphylina extracts against H. pylori, scrutinising the whole plant and matured stem through a comparative pharmacognostic analysis. Utilising herbal standardisation techniques, we confirm the heightened purity of the powder. Antimicrobial assessments show exceptional efficacy of DME (dried Ethanolic extract of I. staphylina) and HLS (hydro alcoholic extract of I. staphylina) extracts. Quercetin isolation by using advanced instrumentation (Nuclear magnetic resonance [NMR], High resolution mass spectrometry [HR-MS], High-performance thin-layer chromatography [HPTLC], Fourier transform infrared spectroscopy [FTIR]) ensures precise compound identification. This methodology guarantees an exhaustive analysis, confirming purity and identifying bioactive components. Standardisation underscores theelevated purity of I. staphylina, with phytochemical screening revealing a predominant presence of phenolics and flavonoids. Antibacterial investigations highlight significant activity, particularly with DME and HLS extracts. These findings substantiate I. staphylina’s medicinal significance, especially its matured stem latex, as a promising treatment for H. pylori-induced stomach ulcers, affirming traditional use by Dharmapuri villagers.